Peningkatan Produktivitas pada Proses Pemilihan Bahan melalui Penerapan Lean Production - Haliawan, Prillia (JURNAL ADMINISTRASI KANTOR, 2023)
This qualitative research was conducted by mapping all activities in the PT.BMT warehouse that do not have added value (non-value added) to productivity and mapping activities that provide added value (added value) to productivity. How to map by implementing the Lean Manufacturing System method through Value Stream Mapping (VSM) analysis and Cause-Effect Diagrams. The implementation of the Lean Manufacturing System method is carried out in the select ingredients process for aluminum die-cast products in the warehouse area of â€‹â€‹PT.BMT Indonesia. The impact of implementing the Lean Manufacturing System method is that the productivity of the select ingredients process increases to 97% through the DHR printing time (areas A, B, C). On the other hand, there was also an increase in the productivity of select ingredients by 34.08% by increasing the number of printers and placing them closer to each material storage area for aluminum die-cast products. The application of lean layout by changing the storage method, which was originally a "U" flow method with a "horizontal" pattern, was changed to a "simple straight" flow method with a "vertical" pattern, was able to reduce processing time by 50% from 1.3 minutes to 0.7 minutes and save space by 29 % due to reduced from 180.1 m 2 to 145.8 m 2   Keywords : Productivity, Lean manufacturing system, VSM, Cause-Effect Diagram